PERBAIKAN PROSES PRODUKSI MENGGUNAKAN GOOD MANUFACTURING PRACTICE (GMP) DAN WORK IMPROVEMENT IN SMALL ENTERPRISES (WISE) PADA IKM KERUPUK SALUYU PUTRA - Panguji Raja Sinurat; Roni Kastaman; Efri Mardawati (Universitas Galuh, 2023)
Currently, there are still many people who have not processed food with due regard to cleanliness and hygiene. Foodborne illness is still a public health problem in Indonesia because of the lack of personal hygiene and environmental sanitation in food preparation and service. This study aims to determine the extent to which GMP-WISE is implemented at IKM Kerupuk Saluyu Putra so that later this business can improve safety and produce hygienic preparations. This research will be conducted on Jl. Raya Barat Cicalengka, Panenjoan, Cicalengka District, Bandung Regency, West Java from December 2021 to November 2022. This research was conducted using the Good Manufacturing Practices and Work Improvement in Small Enterprises (GMP-WISE) method. Data collection used questionnaires, and data analysis used several stages, namely observing current conditions, suggesting improvements, and validating employee knowledge. The results of the hypothesis test show that there is a relationship between the implementation of GMP-WISE and employee hygiene and sanitation knowledge. Production process improvements, GMP-WISE guidelines, and employee training need to be carried out to maintain product safety.